Upaya Meningkatkan Kemampuan Bercerita Melalui Media Gambar Seri Pada Anak Kelompok B - Rismawati Rismawati; Bastiana Bastiana; Ramlah Ramlah (Universitas Negeri Makassar, 2022)
This study aims to determine the improvement of the speech skills of kindergarten students in terms of telling stories or responding to teacher questions. In this case, the child's ability is lacking due to the teacher's lack of stimulus, the image media used by the teacher is less attractive and not varied, or the child's environment is less supportive. The research was carried out at the Sulawesi Kindergarten which is located at jalan tupai no.98 kelurahan labuang baji, mamajang district Makassar. It was carried out in group B with 14 children divided into eight boys and six girls. The problem-solving in group B is carried out using the media of a series of images made by the teacher. The objective is to (a) describe the use of illustrated media and (b) describe the increase in children's speaking activities, especially storytelling through image media. (c) present the results of improving children's speaking skills, especially in terms of storytelling, after learning with series image media, Data collection using learning and observation results. The collected data were analyzed by descriptive analysis. And obtained an average score, in cycle I, the ability to speak and respond to children was 28.87%, cycle II became 57.14%, and in the third cycle, it became 64.26%. From the results of these percentages, series image media can improve children's participation skills with the support of varied and exciting methods and involve children in each activity.